(untitled) (Medico Legal Update, 2021)
Background: Gingival enlargement is one of the frequent features of gingival diseases. Inflammation of the gingival tissues can be induced by diverse method. All changes in gingival tissues express with some degree of inflammation. In some cases, where gingival enlargement could be the primary sign of potentially lethal systemic diseases, a correct diagnosis of these enlargements could prove life saving for the patient or at least initiate early treatment and improve the quality of life. Pertinent management depends on precisely diagnosing the origin of enlargement. The aim of publishing this case report is to present the clinical, histopathological features and treatment of inflammatory gingival enlargement which disturbed the aesthetics and masticatory function of the patient. Method: A 20 year old female patient reported with a chief complaint of swelling in the gums of teeth in lower front region. The enlargement was soft and friable and bleeding spontaneously making it difficult for the patient to maintain adequate personal oral hygiene. Surgical therapy was carried out to provide a good aesthetic outcome. Conclusion: No recurrence was reported. Gingival overgrowth is unaesthetic, and may interfere in mastication and speech; hence a thorough understanding of the pathogenesis is essential for management.